2009
DOI: 10.1177/154193120905301120
|View full text |Cite
|
Sign up to set email alerts
|

A Communication Analysis Methodology for Developing a Cardiac Operating Room Team-Oriented Display

Abstract: This paper outlines an empirical method to analyze human communication in the context of a cardiac Operating Room (OR) and derive design requirements for a team-oriented information display. Its first phase was to identify and categorize shared information within teamwork. The subsequent analysis of the shared information included aggregating shared information instances into unique items, and then scoping and generating the display requirements. The analysis resulted in 52 unique shared information items out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, not everyone in the team needs to see everything all the time. Display only what at least two team members require to support them in their teamwork at any given time (Parush et al, 2009).…”
Section: Scope and Prioritize The Information To Be Displayedmentioning
confidence: 99%
“…However, not everyone in the team needs to see everything all the time. Display only what at least two team members require to support them in their teamwork at any given time (Parush et al, 2009).…”
Section: Scope and Prioritize The Information To Be Displayedmentioning
confidence: 99%
“…Furthermore, previous in-hospital communication research (Foster-Hunt, 2009;Kramer, 2009;Parush et al, 2009) has observed similar scenarios and produced useful findings that have been applicable across healthcare settings.…”
Section: Study Limitationsmentioning
confidence: 68%
“…Relationship between the number of utterances per handoff and the complexity of each handoff.Verbal behaviour typesCategories describing the type (e.g., purpose) of communication were based on conversation analysis adapted from Pomerantz & Fehr (1997),Parush et al (2009), andKramer (2009), combined with categories that emerged through data coding. This method produced eight high-level categories: seeking information, responsive information, offering information, proactive information/report, requesting information, educating, comments, and irrelevant information.…”
mentioning
confidence: 99%